PENGARUH HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA UD. OVI KECAMATAN LUAHAGUNDRE MANIAMOLO KABUPATEN NIAS SELATAN - Sihuhra, Cerita (LPPM Universitas Nias Raya, 2022)
This study aims to determine the effect of Product Prices on consumer purchasing decisions on UD. Ovi subdistrict luahagundre maniamolo district south nias. This type of research is a quantitative research that is associative with the object under study is all consumers contained in UD. Ovi subdistrict luahagundre maniamolo district south nias has as many as 30 people. The result of this indicatesdicate that communication affects consumer purchasing decisions, which is indicated by the thing hitung (7,062) > ttabel (1,701) and the significant level 0,000 < 0,05. Retrieved value R2 of 0,640 (50,125%) ie decision-making purchasing decision on UD. Ovi subdistrict luahagundre maniamolo district south nias can be explained by independent variabel of communication. While the rest of 49,875% it is explained by other variables outside the model. From the result of the discussion, it can be seen that Product Prices are one of the important elements of marketing and also influence consumer decision to buy.